2006
DOI: 10.1364/ol.31.000065
|View full text |Cite
|
Sign up to set email alerts
|

Laser and self-Raman-laser oscillations of PbMoO_4:Nd^3+ crystal under laser diode pumping

Abstract: Different regimes of laser operation and stimulated Raman scattering (SRS) for a laser diode (LD)-pumped PbMoO4:Nd3+ crystal have been investigated. Under 1.5 W LD pumping, the output power of the PbMoO4:Nd3+ laser in the free-running mode at 1056 nm reached 0.65 W with a slope efficiency of up to 53%. Using different LiF: F-2 saturable absorbers, we achieved a maximum pulse energy of 11 microJ at a 1.4 ns pulse duration and a maximum output power of 0.35 W (10 microJ) at a 7 ns pulse width in the passively Q-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(13 citation statements)
references
References 5 publications
0
13
0
Order By: Relevance
“…For this crystal the situation is similar to that of the PMO:NaNd(MoO 4 ) 2 crystal-two or more defect clusters containing two crystallographic positions of Nd 3 + could be produced. 3 : This crystal with lower Nd 3 + concentration is characterized by one time of Nd 3 + luminescence decay and one magnitude of activation energy. On increasing the Nd 3 + concentration the second decay time appears and activation energy changes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For this crystal the situation is similar to that of the PMO:NaNd(MoO 4 ) 2 crystal-two or more defect clusters containing two crystallographic positions of Nd 3 + could be produced. 3 : This crystal with lower Nd 3 + concentration is characterized by one time of Nd 3 + luminescence decay and one magnitude of activation energy. On increasing the Nd 3 + concentration the second decay time appears and activation energy changes.…”
Section: Resultsmentioning
confidence: 99%
“…SRS spectroscopy showed that lead molybdate PbMoO 4 (PMO) and lead tungstate PbWO 4 (PWO) crystals with a scheelite-type structure (tetragonal system, C 4h 6 space group) belong to the most promising matrices for use as active laser elements with self-SRS conversion [1,2]. Under laser diode pumping, laser generation and simultaneous SRS conversion were realized for both PWO:Nd 3 + and PMO:Nd 3 + crystals [3,4]. To generate the Stokes components, SRS lasers require higher pump powers.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the availability of the material parameters, we used the derived analytical expressions to characterize thermal lens in three tetragonal sheelite-type molybdates, Nd:PbMoO 4 , Nd:CaMoO 4 and Nd:NaBi(MoO 4 ) 2 . These crystals were intensively studied for the use in DPSSLs with Raman selfconversion [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…These systems are simple and versatile, and by choosing different laser and Raman crystals, a range of output wavelengths can be obtained for potential applications in the areas of medicine, biomedicine, and remote sensing. Systems which are particularly useful are self-Raman compact lasers based on Nd-doped laser crystals that provide the first Stokes line in the near infrared region between 1100 and 1200 nm [1][2][3][4][5][6][7]. Combined with frequency doubling, these laser sources generate radiation at wavelengths in the yellow-orange spectral region.…”
Section: Introductionmentioning
confidence: 99%